Kriteria Keamanan Blok Cipher dan Analisis Sandi Diferensial - Yusuf Kurniawan; M. Sukrisno Mardiyanto; Iping Supriana Suwardi (Teknoin, 2005)
Several criterions used to determine the security measure of ciphers, have been researched for tens years. Shannon recommended two concepts for designing of algorithm encryption: confusion and diffusion. These criterions have been expanded with other criterions addition like avalanche property, Strict Avalanche property, Key-dependence avalanche, sequence complexity, Binary derivatives, and Bit dependencies. This paper will try to discuss if the criterions that have been proposed by researchers have succeeded to counter to cryptanalysis. In this paper, six-round-DES is examined. The result of the research showed that the DES reduced to six rounds has satisfied the criterions, but failed to counter to differential cryptanalysis (DC). Some researchers have proposed to strengthen DES by making all subkeys Ki independent. So, for DES reduced to six rounds with independent subkeys, the number of keys is 6x48 (288 bits). However, DC can break the cipher by analyzing only 256 cipher texts.Keywords: Block cipher, differential cryptanalysis, DES, criterions, subkey.